(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Neonatal hypothermia increases morbidity and mortality . This study aimed to assess the incidence of neonatal hypothermia and its association with low birth weight, preterm delivery, APGAR score and nursing care practices. Methods: A cross-sectional analytical study was carried out to assess the neonatal hypothermia in neonates born via vaginal deliveries at Maternity ward of Patan hospital, Patan Academy of Health Sciences (PAHS), Nepal, during Aug–Sept 2018. The study was approved from institutional review committee of PAHS. Axillary temperature was measured 4 times, at ten minutes and at 1,2, 4 hours after delivery by using Micro Life digital thermometer. The SPSS was used to analyse data for association of hypothermia with low birth weight, preterm delivery, APGAR score and nursing care practices. Chi square and fisher exact tests were used and p<0.05 was considered significant. Results: Out of 153 neonates, neonatal hypothermia was seen in 61 (39.8%), 66 (43.1%), 52 (33.9%) and 41 (26.8%) at 10 minutes and 1, 2 and 4 hours after delivery. There was statistically significant association between APGAR score and hypothermia at 1 hour. There was significant association between nursing care practices after delivery and hypothermia at 4 hours. Conclusions: In this study, the incidence of neonatal hypothermia was highoccurringin40% at 10 minutes and 25% at four hours after delivery. Low APGAR score was associated with hypothermia.